Costal pathology after radical treatment for breast cancer - M. P. Vavilov; A. V. Martynenko (Опухоли женской репродуктивной системы, 2014)
This is the first description of upper rib block occurring as a complication due to surgical and radiation therapy in 64% of 136 patients with verified breast cancer. Procedures for manual diagnosis and treatment of costal block are outlined. The mechanisms responsible for the pathogenesis of costal pathology are considered in the context of protective myofixation of the humeroscapular region and thoracic outlet syndrome.